Patient-based reliability of the Outcome Measures in Rheumatology (OMERACT) ultrasound scoring system for salivary gland assessment in patients with Sjögren's syndrome - Finzel, Stephanie; Jousse-Joulin, Sandrine; Costantino, Félicie; Hánová, Petra; Hocevar, Alojzija; Iagnocco, Annamaria; Keen, Helen; Naredo, Esperanza; Ohrndorf, Sarah; Schmidt, Wolfgang A; D'Agostino, Maria Antonietta; Terslev, Lene; et al. (Rheumatology (Oxford, England), 2021)
BACKGROUND: To assess the reliability of the consensually agreed US definitions of major salivary gland lesions and the US scoring system for salivary gland assessment in patients with SS. METHODS: Nine experienced sonographers scanned and read the US images of both parotid glands (PGs) and submandibular glands (SMGs) in eight patients with primary and secondary SS in two rounds. A consensually agreed four-grade semi-quantitative scoring was applied in B-mode for morphological lesions: grade 0, normal; grade 1, mild inhomogeneity without anechoic or hypoechoic areas; grade 2, moderate inhomogeneity with focal anechoic or hypoechoic areas; grade 3, severe inhomogeneity with diffuse an- or hypoechoic areas occupying the entire gland or fibrous gland. The presence or absence of typical SS lesions, i.e. the Sjögren's signature, was scored binary. Intra- and interreader reliabilities were computed using weighted and unweighted Cohen's and Light's κ coefficients. RESULTS: The mean prevalence of grades 0-3 in PG were 43, 17, 23 and 31% and 28, 14, 33 and 32% for the SMGs, respectively. The weighted κ for intrareader reliability ranged from 0.44 to 1 for grading and 0.64 to 1 for the Sjögren's signature of PG and 0.59 to 1 and -0.09 to 0.6 for SMGs, respectively. The interreader reliability κ for grading in PG was 0.62 (95% CI 0.47, 0.74) and for Sjögren's signature it was 0.36 (95% CI 0, 0.43); in SMG it was 0.62 (95% CI 0.47, 0.72) and 0.03 (95% CI 0, 0.07) respectively. CONCLUSIONS: The consensually agreed novel US scoring system for major salivary gland lesions showed substantial intra- and interreader reliability in patients with SS. The reliability of the Sjögren's signature was moderate.
Keywords: ultrasound; Humans; lidé středního věku; hodnocení výsledků zdravotní péče; salivary glands; Female; Aged; Sjogren's Syndrome; dospělí; Sjögren’s syndrome; scoring system; Ultrasonography; senioři; lidé; Sjögrenův syndrom; parotis; reprodukovatelnost výsledků; Adult; Parotid Gland; ultrasonografie; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Submandibular Gland; reliability; mužské pohlaví; Outcome Assessment, Health Care; podčelistní slinná žláza